2007
DOI: 10.1902/jop.2007.070115
|View full text |Cite
|
Sign up to set email alerts
|

SPARC Gene Polymorphism in Renal Transplant Patients With Gingival Overgrowth

Abstract: No association between SPARC gene polymorphism and gingival overgrowth was revealed in kidney transplant patients who were administered CsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Osteonectin has been considered as a bone formation marker however its function is still unclear. To the best of our knowledge, there are very limited numbers of studies investigating osteonectin protein in periodontal diseases and none of them questioned its role in peri‐implant diseases. In the present study, we were expecting a change in PISF osteopontin levels in especially implants with peri‐implantitis because of its role in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Osteonectin has been considered as a bone formation marker however its function is still unclear. To the best of our knowledge, there are very limited numbers of studies investigating osteonectin protein in periodontal diseases and none of them questioned its role in peri‐implant diseases. In the present study, we were expecting a change in PISF osteopontin levels in especially implants with peri‐implantitis because of its role in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated specific polymorphisms as risk factors for the development of gingival overgrowth. While studies on MMP‐1, interleukin‐6 and the drug transporter MDR1 gene have failed to identify any association with gingival overgrowth (18–21), other studies have identified clear associations between gingival overgrowth and polymorphisms in α2 integrin, transforming growth factor‐β1 and interlukin‐1 (22–24). Serum levels of transforming growth factor‐β1 have been shown to be a significant indicator of the risk of developing gingival overgrowth (25).…”
Section: Discussionmentioning
confidence: 99%